Soft Skill Development Through Career Counseling Programs to Face The Challenges of The Work Industry for Students - Nur Inyatun Nisa (Eduvest - Journal of Universal Studies, 2025)
This article aims to examine and understand the development of students' soft skills through career counseling programs so that they can be better prepared to face challenges in the work industry. The approach method used in this study is library research with a descriptive analysis method. Researchers collected data from a variety of written sources, including articles, theses, relevant journals, books, and documents, as well as online sources with a focus on keywords such as "soft skills," "career counseling programs," and "job industry challenges." The data that has been successfully collected is then processed, interpreted, classified, analyzed, and concluded to obtain a relevant conclusion. The data analysis technique used is descriptive analysis. Test the validity of the data for the extension of observations, increase persistence, and triangulation. The study results show that an effective career counseling program can improve students' soft skills, which is very important to meet the demands of an increasingly competitive workforce. The program also assists students in exploring career options and preparing to enter the job market. The conclusion of this study emphasizes the importance of soft skill development through career counseling programs as a strategy to prepare students to face challenges in the industrial world. This program is expected to make a positive contribution to student work readiness.